2016
DOI: 10.1192/bjp.bp.114.160192
|View full text |Cite
|
Sign up to set email alerts
|

Premature mortality in autism spectrum disorder

Abstract: Premature mortality was markedly increased in ASD owing to a multitude of medical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
618
8
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 699 publications
(702 citation statements)
references
References 32 publications
27
618
8
14
Order By: Relevance
“…The increased ratio of the prevalence of males to females with ASD is well-established (Lai et al 2013) as is the fact that males have a higher rate of suicide than females in the general population (Hawton 2000). However, in contrast to the increased risk of suicide in males in the general population, a recent study reported a loss of this typical sex difference, leading to a higher relative risk in females with ASD compared to those without ASD (Hirvikoski et al 2016). Over the last few years, an increased awareness of sex differences in brain and behaviour studies in ASD is an encouraging trend (Alice et al 2007;Baron-Cohen et al 2011;Lai et al 2013;Mandy et al 2011) that should be extended into the matrix of ASD and suicidality.…”
Section: Developmental-contextual Factors: Sex and Agementioning
confidence: 81%
See 1 more Smart Citation
“…The increased ratio of the prevalence of males to females with ASD is well-established (Lai et al 2013) as is the fact that males have a higher rate of suicide than females in the general population (Hawton 2000). However, in contrast to the increased risk of suicide in males in the general population, a recent study reported a loss of this typical sex difference, leading to a higher relative risk in females with ASD compared to those without ASD (Hirvikoski et al 2016). Over the last few years, an increased awareness of sex differences in brain and behaviour studies in ASD is an encouraging trend (Alice et al 2007;Baron-Cohen et al 2011;Lai et al 2013;Mandy et al 2011) that should be extended into the matrix of ASD and suicidality.…”
Section: Developmental-contextual Factors: Sex and Agementioning
confidence: 81%
“…Recent reports have drawn attention to the high prevalence of suicidality in individuals with autism spectrum disorder (ASD) (Cassidy et al 2014) and a sevenfold increase in the number of deaths by suicide in the ASD population compared to the general population (Hirvikoski et al 2016). Along with the increased prevalence of co-occurring mental health problems in individuals with ASD (50-70%; Simonoff et al 2008), it is pressing to understand the interplay of ASD symptomology and suicidality in order to offer better care.…”
Section: Introductionmentioning
confidence: 99%
“…Their risk of death was still estimated to be twice that of their matched controls without ID (HR 2.2; see Table 23). A doubling of mortality risk with autism spectrum disorder compared with the general population has been shown in several population cohorts worldwide; 131 however, this risk increases in studies that were able to further restrict the comparison to subjects with a co-existing ID 131 or neurological disorders. 132 Although a recent large Swedish case-control study 131 reported an OR of 5.8, the median age of death for the group with co-existing ID (40 years) suggests that insufficient follow-up in our study (3 years) may account for our imprecise findings among the younger subgroup of adults with ID with autism, who had an average age of only 30.5 years at the beginning of follow-up.…”
Section: Mortalitymentioning
confidence: 99%
“…Many studies originating in Scandinavian and the Nordic countries [20] have previously used hospitalisation rates [21,22], as well as, individual uptake of psychotropic medication to examine a range of factors, including maternal and pre-natal factors related to attention-deficit/hyperactivity disorder in children [23,24], factors related to impaired psychological health in adolescents and younger adults [25], area effects on psychiatric morbidity [26], the effects of working conditions and early retirement [27,28] and the prevalence and differences in poor mental health across refugees and migrants [29]. Medical records have also been used in validity studies of self-reported medication use, with reports of good agreement and specificity being noted between the two measures, especially in chronically used medicines [30].…”
Section: Introductionmentioning
confidence: 99%